Evolution and significance of banking distribution channels - Jóźwiak, Marcin (Journal of Finance and Financial Law, 2025)
The purpose of the article. The aim of this article is to present and evaluate the distribution channels used by retail banks, the determinants of banks' choice of these channels, and the directions of changes. The study will seek to answer the research question of what the evolution of distribution channels for banking products and services entails and what determines it. Methodology. In analysing the banking distribution channels, the method of review and critical, descriptive and comparative analysis of the literature and reports of the banking sector was used. Results of the research. Changes in distribution channels have been presented, from the basic model of distribution known for many years, which is the bank branch, to modern multichannel and omnichannel models. Using the example of changes in customer approach to the increasing use of the Internet and mobile applications in banking, the directions of changes in the banking sector's approach to the use of available distribution channels have been shown. The shift of customers from bank branches to the Internet and mobile applications, where customers have already learned to perform simple banking operations, has forced changes in the banking sector. Directions in the banking sector's move away from traditional brick-and-mortar branches towards combining them with other channels such as call centers, the Internet, or mobile applications to reduce costs and increase business efficiency have been indicated. Banks, by reducing costs and adapting to the observed trend of customers moving to remote channels, are beginning to reorganize their distribution network, including the bank branches themselves.